Humans and Machines at Work Monitoring, Surveillance and Automation in Contemporary Capitalism (Dynamics of Virtual Work, 2018)
In the era of the so-called Fourth Industrial Revolution, we increasingly work with machines in both cognitive and manual workplaces. This collection provides a series of accounts of workers' local experiences that reflect the ubiquity of work's digitalisation. Precarious gig economy workers ride bikes and drive taxis in China and Britain; domestic workers' timekeeping and movements are documented; call centre workers in India experience invasive tracking but creative forms of worker subversion are evident; warehouse workers discover that hidden data has been used for layoffs; academic researchers see their labour obscured by a 'data foam' that does not benefit them; and journalists suffer the algorithmic curse. These cases are couched in historical accounts of identity and selfhood experiments seen in the Hawthorne experiments and the lineage of automation. This collection will appeal to scholars in the Sociology of Work and Digital Labour Studies and anyone interested in lea rning about monitoring and surveillance, automation, the gig economy and the quantified self in the workplace.